Upper lip myomucosal flap for the repair of anterior oronasal fistula. Issue 3 (July 2018) - Elsherbiny, Mohamed; Saed, Basem; Sheir, Hesham; Elzohiri, Mohamed; Asharf, Tamer; Elshafey, Abdelrahman; El-Ghazaly, Mohamed
Abstract : Anterior oronasal fistula after cleft palatal repair is difficult to correct and it is consider challenging to many surgeons. Many techniques were used to repair this type of fistula without guarantee for success. Upper lip myomucosal flap is an alternative technique for the repair of this type of fistula. This is a retrospective descriptive case series study which included 10 patients diagnosed with anterior oronasal fistula after cleft palatal repair. They presented to Pediatric Surgery Department at the Faculty of Medicine, Mansoura University Children Hospital from the period between November 2013 and August 2014. In this technique, we do harvesting of the flap with measurement of its length and width, then baring the edge of the fistula with trying of its closure with local flaps. After that we suture the flap to the edge of the fistula and then evaluate the success rate. This study included 10 patients with age ranging from 15 to 72 months. The size of the fistula was less than 1 cm in six patients and more than 1 cm in four patients. The flap was used as an additional layer repair in seven patients and as the only layer for the repair in three patients. This technique was found to be successful in 70% of the patients with good healing without any recurrent fistula. We concluded that the use of this technique is feasible; however, its efficacy should be tested in larger number of patients to be considered as an option for the treatment of anterior oronasal fistula.